Development of Bacteriology Textbook based on Research on Mn Bioremediation in Bacteriology Course - Rizki Pratama; Mimien Henie Irawati Al Muhdhar; Ibrohim (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to produce a textbook based on the results of the research on the ability of bacteria to degrade heavy metals. The research was conducted using the ADDIE model with a series of tests such as a validity test, practicality test, and textbook effectiveness test. The textbook is validated by 3 experts: learning experts with a score of 91% (valid), materials experts with a score of 100% (valid), and practitioners with a score of 95% (valid). Practicality test using student responses from individual test (score 89%), small group test (score 90%), and field test (score of 89%). The effectiveness test of textbooks using an experimental method with a one-group pretest-posttest-only design by comparing the pretest and posttest scores using the Wilcoxon test and the N-Gain test. The Wilcoxon test results showed a significance value obtained smaller than 0.05 (p-value (0.000) < 0.05), this shows that there is a significant influence between the pretest and post-test scores. The N-Gain results were at a score of 0.4, which means that the improvement experienced by students was at a moderate level. Based on the validity, practicality, and effectiveness scores, it can be concluded that the textbooks are valid, practical, and effective.